PENGUATAN KARAKTER SISWA MELALUI PROGRAM WAWASAN KEBANGSAAN BERBASIS KOLABORASI LINTAS SEKTOR - Ruslina Dwi Wahyuni; Amir Mukminin (AL HAZIQ: Journal of Community Service, 2025)
This community service program aims to socialize national insight and strengthen the Pancasila Student Profile character among new students at SMPN 1 Wuryantoro, Wonogiri Regency. The background of this activity is the increasing ideological challenges, weakening nationalism values among adolescents, and the need for character reinforcement at the beginning of school education. The partner’s problems include low understanding of Pancasila values, lack of civic responsibility awareness, and limited collaboration between schools and state institutions. The method applied was an educative-participatory approach through interactive lectures, group discussions, value simulations, and character reflections, involving lecturers from STAIMAS Wonogiri and the Wuryantoro Police Sector. The results indicate a significant improvement in students’ understanding of national values, nationalism attitudes, and legal awareness. This activity also strengthened collaboration among universities, schools, and police institutions in shaping a generation with strong Pancasila character.